"La beauté est dans la rue": Four reasons (or perhaps five) to study crowds. (September 2017) - Reicher, Stephen
In this paper, I argue that the study of crowds provides important lessons for social psychology in four key areas. First, it reveals the political influences which shaped and continue to shape the questions we ask and the answers we provide. Second, it demonstrates the importance of a methodological strategy which attends to real-world phenomena and the ability of theory to make sense of them. Third, it generates new theoretical insights and conceptual paradigms which have relevance to social psychology in general. Fourth, it provides new insights into the way that the social relations which constitute everyday social reality are created, consolidated, and changed. In sum, I suggest that the crowd is uniquely fertile ground in which to investigate the subject matter of social psychology.